1985
DOI: 10.1093/bja/57.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacology of the Ketamine Isomers

Abstract: The clinical and electroencephalographic (EEG) effects of the individual ketamine isomers were compared with the racemic mixture in five volunteers who received each drug on a separate occasion. Racemic ketamine 275 +/- 25 mg, s(+) ketamine 140 +/- 21 mg or R(-) ketamine 429 +/- 37 mg produced an anaesthetic state lasting 6 +/- 2 min (mean +/- SD). However, the EEG evaluation of the R(-) isomer revealed less overall slowing, and an absence of the large slow wave complexes produced by the S(+) isomer and the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
206
1
17

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(233 citation statements)
references
References 12 publications
9
206
1
17
Order By: Relevance
“…There is also more rapid recovery of psychomotor function and performance. [3][4][5] Studies in laboratory animals have shown that racemic ketamine exhibits some neuroprotective potential when infused prior to incomplete cerebral ischemia or following traumatic brain injury. [6][7][8][9] For example, studies in this animal model of incomplete hemispheric ischemia have shown that neurological outcome was improved at three days from insult with racemic ketamine.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…There is also more rapid recovery of psychomotor function and performance. [3][4][5] Studies in laboratory animals have shown that racemic ketamine exhibits some neuroprotective potential when infused prior to incomplete cerebral ischemia or following traumatic brain injury. [6][7][8][9] For example, studies in this animal model of incomplete hemispheric ischemia have shown that neurological outcome was improved at three days from insult with racemic ketamine.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…We asked if the benefits of S(+)ketamine reported for other species (Ryder et al 1978, White et al 1985, Pfenninger et al 2002, Strümper et al 2004 regarding its clinically apparent potency, overall quality of anesthesia and decreased undesirable effects, would have a synergistic effect when associated to propofol. Premedications as well as different degrees of surgical stimulus and the concurrent use of other drugs may complicate comparison of different anaesthetic drugs both at combined administration.…”
Section: Discussionmentioning
confidence: 99%
“…In man, S(+)Ketamine has an anaesthetic-analgesic effect two to four times greater than racemic ketamine (White et al 1985;Mathisen et al 1995;Lauretti et al 2000), and its hyptonic effect is more potent than that of the R(-) isomer (Terra et al 1999), allowing the use of lower doses of S(+) ketamine compared to racemic ketamine.…”
Section: Introductionmentioning
confidence: 99%
“…
In der zunächst veröffentlichten OnlineVersion des Beitrags wurden falsche Angaben zur Dosierung von S-Ketamin gemacht.Ketamin und das verwandte S-Ketamin können beide intranasal mittels MAD-Device verabreicht werden.Verschiedenste Studien belegen, dass S-Ketamin verglichen zu Ketamin-Razemat in halber Dosierung einen äquivalen-ten Effekt aufweist [1,2,3]. Aus dieser Tatsache heraus sollte auch bei der intranasalen Applikation zunächst mal die halbe Dosierung verabreicht werden.
…”
unclassified
“…Verschiedenste Studien belegen, dass S-Ketamin verglichen zu Ketamin-Razemat in halber Dosierung einen äquivalen-ten Effekt aufweist [1,2,3]. Aus dieser Tatsache heraus sollte auch bei der intranasalen Applikation zunächst mal die halbe Dosierung verabreicht werden.…”
unclassified